Optimiranje akustičke kvalitete profesionalnoga prostora za slušanje: doktorski rad - Krhen, Miljenko; Fajt, Siniša (Zagreb: M. Krhen ; Fakultet elektrotehnike i računarstva, 2014)
Doktorski rad „Optimiranje akustičke kvalitete profesionalnoga prostora za slušanje“ rezultat je istraživanja akustičkih svojstava profesionalnih prostora za slušanje. Utvrđene su posebnosti tih prostora koje karakterizira vrlo velika važnost kvalitete zvuka u svrhu njegove obrade, pri čemu oni moraju biti akustički tako projektirani da vrijednosti svih njihovih parametara akustičke kvalitete imaju optimalne vrijednosti potrebne za postizanje najbolje moguće kvalitete slušanja. Izmjereni su realni profesionalni prostori za slušanje, i nakon toga je napravljena detaljna statistička analiza izmjerenih vrijednosti parametra, kao i rezultata subjektivnih ispitivanja, i to primjenom statističke metode analize glavnih komponenata i statističke metode združene analize parametara. Tim metodama utvrđeni su uvjeti mjerenja pod kojima se dobivaju najtočniji rezultati mjerenja, koji će u najvećoj mjeri korelirati sa subjektivnim ocjenama istih tih prostora. Matematičkom metodom združenih parametara određeni su koeficijenti utjecaja objektivnih parametara akustičke kvalitete na subjektivnu ocjenu. Nakon toga je napravljen matematički model funkcijske ovisnosti primjenom polinomne i racionalne funkcije koja prikazuje frekvencijsku ovisnost objektivnih parametara za uvjet postizanja optimalne kvalitete slušanja. U konačnici, izveden je i geometrijski model optimalnog prostora za slušanje, koji služi kao osnova za izradu računalnih simulacija u kojima su namjerno, na kontrolirani način mijenjani neki akustički uvjeti, i utvrđene su granice promjene tih određenih parametara akustičke kvalitete kod kojih dolazi do subjektivnih zamjećivanja promjene u kvaliteti slušanja.
Ključne riječi: akustika, akustička kvaliteta, profesionalni prostor za slušanje, tonska režija, analitičke metode, subjektivna ocjena, objektivni parametri, model optimalnog prostora, upravo zamjetljive granice promjene
Ph. D. thesis entitled "Optimizing acoustical quality of sound control room" is the result of the study of acoustic properties of professional sound control rooms. The specificities of these rooms which are characterized by very high importance to have the high quality of sound for the purpose of its processing are determined. They must be acoustically designed so that the values of their acoustical quality parameters have optimal values necessary to achieve the best possible listening quality. The real sound control rooms were measured, and a detailed mathematical analysis of the measured parameter values was done, as well as the analysis of subjective tests results. This analysis was done applying the statistical method “Principal Components Analysis” (PCA) and statistical method “Conjoint Analysis” (CA). With those methods measuring conditions under which they receive the most accurate measurement results are defined, and which will have the best possible correlation with subjective evaluations of the same rooms. The mathematical model of functional dependency by using polynomial and rational functions was made. This model shows the frequency dependence of objective parameters provided to achieve the optimum listening quality. Finally, the geometric model of optimal sound control room is defined. Also, the values are defined, within which certain parameters has the just noticeable value change.
In the introductory chapter an overview of types of professional sound control rooms, their basic characteristics and problems, and their basic design principles are given.
In the second chapter an overview of measurement methods and measuring conditions defined for the purposes of research are given. Also, the objective room acoustic parameters which were considered are described, as well as the method of subjective acoustical quality test. The test conditions are defined and subjective acoustical quality parameters that were considered in the thesis are provided and described.
In the third chapter an analysis of objective acoustical quality parameters for professional sound control rooms is given. Structural parameters (dimensions and volume) of professional sound control rooms are shown, as well as the results of statistical analisys of the objective acoustical quality parameters. A statistical analisys with the method of principal components analysis (PCA) of measurement results in different conditions was made.
In the fourth chapter the subjective parameters of acoustical quality of professional sound control rooms were analyzed. An algorithm for evaluating the acoustical quality of the room with respect to each subjective parameter of acoustical quality of the room is presented. The impact of a certain objective parameters of acoustic qualities of the room on the parameters of a subjective evaluation of acoustic quality is assessed.
In the fifth chapter mathematical model of optimal sound control room is designed. The functional frequency dependence of objective parameters of acoustic quality of the room is determined, where the condition is to achieve the best subjective assessments. The functional dependence is determined by polynomial and rational functions. The geometric model used in computer simulation is also designed.
In the sixth chapter a computer simulation of sound control room is presented. In the simulation some parameters of acoustical quality are changed, and the values where the change is just noticeable are determined.
In the seventh chapter, "Conclusion", all the results of research done in this Ph. D. thesis are summarized.
In this way, the whole objective measurements and subjective assessments of acoustical quality of professional sound control room are completely covered. The mathematic and geometric models for computer simulation are made. Those models and simulations of acoustic properties provide a full image of the problem, and allow us to propose the solutions for the problems of acoustical design of professional sound control rooms. The complex dependencies of the results of the objective measurements and subjective assessments of acoustic quality is shown, as well as the complexity of the optimization process of acoustic parameters in order to achieve the acoustically optimal sound control room.

Keywords: acoustics, acoustic quality, professional sound control room, analytical methods, subjective assessments, objective parameters, the model of optimal sound control room, just noticeable changes
Bibliografija:136-139 str.